2023
DOI: 10.3390/tropicalmed8070343
|View full text |Cite
|
Sign up to set email alerts
|

Theracurmin Modulates Cardiac Inflammation in Experimental Model of Trypanosoma cruzi Infection

Abstract: Theracurmin is a nanoparticle formulation derived from curcumin, a bioactive compound known for its antioxidant and anti-inflammatory properties. Trypanosoma cruzi, the etiological agent of Chagas disease, triggers an intense inflammatory response in mammals and also causes severe tissue damage. To evaluate the immunomodulatory and antiparasitic effects of Theracurmin, Swiss mice were experimentally infected with 103 trypomastigote forms of the Colombian strain of T. cruzi and submitted to daily therapy with 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…A low BNZ dose (750 mg/kg TD) plus PLGA-CUR Nps, reduced cardiac hypertrophy and parasite load, chronic inflammation, fibrosis, and the levels and activities of cardiopathogenic biomarker enzymes and cytokines/chemokines (IL-1β, TNF-α, IL-6, and CCL5), matrix metalloproteinases (MMP-2 and MMP-9), and inducible enzymes (cyclooxygenase and nitric oxide synthase) implicated in leukocyte recruitment and cardiac remodelling [ 76 ]. More recently, Theracurmin ® (a natural product of Theravalues, Tokyo, Japan, that enhances the curcumin bioavailability 30-fold compared with curcumin powder [ 77 78 ]) showed immunomodulatory (reduced CCL2 in cardiac tissue, IL-15 in cardiac and skeletal tissue, plasma creatine kinase, and tissue leukocyte infiltration) and trypanocidal effects (reduction of parasitemia) in an acute murine model [ 79 ]. A complementary use of Theracurmin ® with BNZ therapy is suggested.…”
Section: Reviewmentioning
confidence: 99%
“…A low BNZ dose (750 mg/kg TD) plus PLGA-CUR Nps, reduced cardiac hypertrophy and parasite load, chronic inflammation, fibrosis, and the levels and activities of cardiopathogenic biomarker enzymes and cytokines/chemokines (IL-1β, TNF-α, IL-6, and CCL5), matrix metalloproteinases (MMP-2 and MMP-9), and inducible enzymes (cyclooxygenase and nitric oxide synthase) implicated in leukocyte recruitment and cardiac remodelling [ 76 ]. More recently, Theracurmin ® (a natural product of Theravalues, Tokyo, Japan, that enhances the curcumin bioavailability 30-fold compared with curcumin powder [ 77 78 ]) showed immunomodulatory (reduced CCL2 in cardiac tissue, IL-15 in cardiac and skeletal tissue, plasma creatine kinase, and tissue leukocyte infiltration) and trypanocidal effects (reduction of parasitemia) in an acute murine model [ 79 ]. A complementary use of Theracurmin ® with BNZ therapy is suggested.…”
Section: Reviewmentioning
confidence: 99%
“…Louise and colleagues [28] demonstrated that theracurmin, a nanoparticle formulation derived from curcumin, was able to modulate cardiac inflammation in an in vivo murine model of Trypanosoma cruzi infection.…”
mentioning
confidence: 99%